ONLINE SELLING AND BUYING USING THE PAYLATER FEATURE ON THE SHOPEE APPLICATION FROM AN ISLAMIC - Istiqomah, Santun; Huzaini, Moh.; Jufri, Akhmad (Laboratorium Riset Ekonomi, 2025)
This study aims to analyze the use of Shopee PayLater service and review its suitability with Islamic law, as well as evaluate the extent to which students of the Faculty of Economics and Business, University of Mataram understand the concept of Shopee PayLater in accordance with sharia principles. The research method used is a qualitative approach with data collection techniques through interviews, observation, and documentation to several students who use the service. The results showed that the buying and selling system using Shopee PayLater was considered not in accordance with the provisions in Islamic law. Although it has fulfilled the elements of the pillars and conditions in the qardh contract, in practice this service contains elements of usury, both qardh usury in the form of additional loans, as well as nasi'ah usury in the form of late fees that are quite high and burdensome for consumers, thus making the contract haram in shari'i. In addition, there are still many students who do not deeply understand Islamic law related to digital financial transactions such as Shopee PayLater. In fact, some who are aware of the element of usury still choose to use it to fulfill their urgent needs. Keywords: Online Selling and Buying, Shopee PayLater, Riba, Qardh, Islamic Law